Dimethylacetamide and trehalose for ram semen cryopreservation - Bittencourt, Rodrigo Freitas (2018)
Eighteen semen samples from nine Santa Ines rams were cryopreserved in order to study the cryoprotective capacity of dimethylacetamide (DMA) at two concentrations (3% and 6%), and its interaction with trehalose (TRE, 100 mOsmol). A further objective of this study was to evaluate in vivo fertility of ram semen cryopreserved with dimethylacetamide. The control treatment was an extender medium with 6% glycerol (GLY). Five treatments were examined: 6% GLY, 3% DMA, 6% DMA, 3% DMA + TRE, and 6% DMA + TRE. After thawing, the kinetic sperm parameters were analyzed using a computerized system. Sperm viability was observed using a multiple parameter sperm staining with propidium iodide (for plasmatic membrane integrity), JC-1 (for mitochondrial membrane potential), and FITC-PSA (for acrosomal integrity). The isosmotic extender with GLY was the most effective medium for the maintenance of sperm characteristics, compared to extenders containing DMA as cryoprotectant. Regarding fertility, the extender medium with 3% DMA may be a safe alternative for sperm cryopreservation, and does not compromise the fertility rates. The addition of TRE decreased the kinetic sperm parameters; however, a positive effect on the integrity of the plasmatic and acrosomal membranes was observed.